Effectiveness of PhET Interactive Simulation-Based Learning on Grade XI Students' Conceptual Understanding of Projectile Motion - Suherman, Wawan; Kariadinata, Rahayu; Chusni, Muhammad Minan (CAHAYA: Journal of Research on Science Education, 2025)
This study addresses the fundamental question: How effective is PhET Interactive Simulation in enhancing high school students' conceptual understanding of projectile motion, a topic prone to misconceptions due to its two-dimensional vector analysis? Positioned within improving physics education quality through digital visualization tools, the researcher employed a quantitative pre-experimental one-group pretest-posttest design on n = 35 Grade XI students. Data collection used conceptual understanding tests analyzed via normality tests (Kolmogorov-Smirnov/ Shapiro-Wilk), paired sample t-test, and Normalized Gain (N-Gain). Results showed pretest mean = 43.76 (SD=12.15) increased to posttest mean =74.14 (SD = 11.72), a 69.42% gain with t = -13.581 (df = 34, Sig. = 0.000 < 0.05) rejecting H₀. N-Gain ⟨g⟩ = 0.54 (medium) distributed as 60% medium, 25.71% high (≥0.7), 14.29% low (<0.3). PhET’s real-time manipulation of launch angle (θ) and initial velocity (v₀) visualized independent horizontal-vertical motion, correcting 65-75% misconceptions via multimodal representations (trajectory, v-t graphs, constant vertical g-vectors). Conclusion: PhET Interactive Simulation proves effective for projectile motion conceptual understanding, bridging abstract formulas (R = v₀²sin2θ/g) with dynamic phenomena. Limitations: short 4-day intervention, no control group. Recommendations: teacher training, guided inquiry worksheets targeting N-Gain > 0.7.